2012
DOI: 10.1177/1321103x12442994
|View full text |Cite
|
Sign up to set email alerts
|

‘Now can I watch my video?’: Exploring musical play through video sharing and social networking in an early childhood music class

Abstract: The purpose of this research was to explore factors influencing musical play of preschool children in home and class settings through the use of video sharing by parents and teacher in an early childhood music course. Six families, all of whom had participated in at least one semester of prior research, attended a 45-minute music class each week for nine weeks and completed and documented assignments via a private online social network. Research questions explored musical play-enhancing and play-inhibiting fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…How can a more competent participant, such as a teacher, contribute, if at all, to children's development in play activities? Koops (2012) studied what enhances and inhibits children's musical play and found that adults can contribute in both respects. It is important that children keep their agency; adults should not become too involved and take control, for example, by giving too many suggestions.…”
Section: Discussionmentioning
confidence: 99%
“…How can a more competent participant, such as a teacher, contribute, if at all, to children's development in play activities? Koops (2012) studied what enhances and inhibits children's musical play and found that adults can contribute in both respects. It is important that children keep their agency; adults should not become too involved and take control, for example, by giving too many suggestions.…”
Section: Discussionmentioning
confidence: 99%
“…Centering on lyrics generally characterizes the initial stage of acquisition of vocal musical skills (Welch, 1994). The earliest children's non-imitative singing surprisingly resembles an ekmelic PS with its stretchable intervals, formulaic structure with retexted lyrics, and private musicking to accompany various activities (Moog, 1976;Dowling, 1984;Bjørkvold, 1992;Campbell, 1998;Barrett, 2011;Koops, 2012). By 7 months, infants can differentiate the timbre of complex tones (Trehub et al, 1990) and remember timbre-specific information (Trainor et al, 2004).…”
Section: Example-14mentioning
confidence: 99%
“…Early childhood music literature contains multiple examples of a connection between enjoyment and children's music making (Andang'o, 2009;Gluschankof, 2008;Koops, 2012Koops, , 2014Suthers & Niland, 2007). However, a search of the literature shows few occasions where researchers set out to study enjoyment within musical interactions.…”
Section: A Look At the Literaturementioning
confidence: 99%